Clinical Evaluation of Hyperimmune Serum for the Treatment of Newcastle Disease in Indigenous Layer Birds (Progressive Agriculture, 2014)
The efficacy of hyperimmune serum for the treatment of Newcastle disease (ND) was evaluated in indigenous birds. A total of 20 indigenous birds (3 to 4 months old) were divided into three groups, namely group A (n = 9), B (n = 8) and C (n = 3). Birds of all the groups were infected orally with 0.2 mL (106.5EID50/0.1 mL) of virulent Newcastle disease virus (NDV). Birds of group A were treated with hyperimmune serum (raised in chickens against NDV) @ 2 mL/bird IM after 6 hours of infection before commencement of clinical signs. Birds of group B received two doses of hyperimmune serum, first @ 2 mL/bird IV after commencement of clinical signs and second @ 3 mL/bird IM 5 hours after first dosing. Birds of group C served as infected control. Birds of group A did not show any clinical signs of ND except one (11%). However, the only sick bird recovered after one repeat dosing of 1 mL hyperimmune serum. In group B, 87.5% birds survived with two birds having nervous signs. Therefore, it may be concluded that hyperimmune sera was effective in preventing morbidity and mortality due to ND in birds when administered before or after commencement of the clinical signs. However, it is needed to conduct a field trial to explore the efficacy of hyperimmune sera raised both in chickens and rabbits.DOI: http://dx.doi.org/10.3329/pa.v24i1-2.19103 Progress. Agric. 24(1&2): 79 - 84, 2013